Implementation Of AI-Assisted Njombangan Visual Interactive Media As A Local Cultural Education For Children at KB Alfi Munir - Kinanti Erste Panggayuh Putri; Bentar Candra Perdana Perdana; Shabrina Fitria Az Zahra Zahra; Azzahra Maycca Yunizar Yunizar (SWAGATI : Journal of Community Service, 2026)
In the Early Childhood Education (PAUD) curriculum, the use of digital media in learning is necessary to adapt to technological developments and be able to create a mindful, meaningful, and joyful learning experience. However, KB Alfi Munir Jombang as an early childhood education institution is still dominated by conventional learning so it is not able to accommodate the characteristics of children as a digital native generation. This community service activity aims to improve the quality of learning through training and implementation of interactive visual learning media "Njombangan" based on Jombang local culture. The program is implemented through teacher training, mentoring media implementation for children through digital storytelling activities, coloring local cultural characters, and interactive digital games based on Jombang local culture. The evaluation of the activity utilizes Artificial Intelligence (AI) as an assistant for user behavior analysis. The results of the activity show an increase in teacher competence in creating simple digital learning media and a very high level of enthusiasm for learning in children. All students were able to complete the coloring activity well and achieved a 100% accuracy rate in the interactive game. The evaluation results showed a User Experience Questionnaire score of 90 (very good category), so the media is proven to be effective in supporting local cultural learning that is more interactive, fun, and adaptive to technological developments.